The Influence of Principal’s Leadership and Work Motivation on Teacher’s Performance - Suharina, Suharina; Ahyani, Nur; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2022)
This study aimed at determining the principal's leadership and work motivation on teacher’s performance both partially and simultaneously. The study was done in SD Negeri Banyuasin I, with 93 teachers as sample. The results obtained indicate that principal's leadership and work motivation on teacher’s performance both partially and simultaneously have significant influence. The research concludes that the principal must focus on his leadership and work motivation of teacher to improve teacher’s performance. This study encourages school principals and teachers to focus on their leadership and work motivation to have good teacher’s performance.